The Effects of Using the Electronic Book “Safe Your Baby” on Caregivers’ Knowledge of Child Rearing and Child Violence Prevention in Preschool Children - Aunchangwang, Wiroonjitra; Suwanwaiphatthana, Wiparat; Prakomnok, Chamaiporn; Niyomsat, Yapat; Padungtan, Vilai (Princess of Naradhiwas University Journal, 2025)
This study was quasi-experimental research with a two-group, pre-posttest design. The purpose of this study was to examine the effects of using the e-book “safe your baby” on caregivers’ knowledge of child rearing and child violence prevention. The sample consisted of 56 caregivers of preschool children (aged 3–6 years) in an urban community in Nakhon Ratchasima Province who met the inclusion criteria. The research instruments included: 1) an e-book titled “Safe Your Baby”, 2) the knowledge about child rearing and child violence prevention questionnaire, and 3) the satisfaction with the e-book questionnaire, which passed the content validity test by finding the index of consistency between the objective questions. The IOC ranged from 0.67 to 1. The reliability was measured by the knowledge questionnaire using the KR-20 to be 0.71 and the satisfaction with the e-book questionnaire using the Cronbach's alpha coefficient to be 0.78. Data were analyzed by using descriptive statistics, the Wilcoxon signed-rank test, and the Mann-Whitney test. The results of the study found that the mean scores of knowledges in child-rearing and violence prevention were significantly higher than before using the e-book (p < .01). The scores in the experimental group were significantly higher than the control group (p < .01). Therefore, Nurses and health care personnel should utilize this e-book to educate caregivers on preventing among children.